THE USE OF LANGUAGE EXPERIENCE APPROACH IN TEACHING READING FOR YOUNG LEARNERS - Dewi Syntiawati Rahayu (Journal of English and Education, 2013)
This study is intended to figure out how Language Experience Approach (commonly abbreviated as LEA) improves students’ motivation and comprehension in reading. The use of this method was chosen as the alternative way in teaching reading for young learners based on its definition. The definition of this method is using students’ experience and knowledge as reading material. This study is an exploratory study which was conducted at one of the English course in Bandung and 6 students were participated in the study. Observation, questionnaires, and interview were employed to gain the data. The data were analyzed both qualitative and quantitative. The results of this study show that the implementation of LEA in teaching learning process was quite successful, despite some limitations of this study. The data gained from students’ show that LEA can help students improve their motivation and reading comprehensions. Most of the students (86, 67%) respond positively towards the use of LEA during the teaching learning process. The data from observation show that the students actively take participation in learning process. The data from questionnaires also reveal that LEA can help the students increase their motivation and confidence in performing language skills. Students also enjoyed the learning process. They were interested and had motivation to learn writing through LEA. Teacher should paid attention to the selection of material, because it influenced the level of students’ motivation and comprehension. The selection of material should be suitable with students’ ability and needs. Based on the findings; it is recommended for further studies that LEA should be implemented in teaching reading at any skills and any educational levels. Keywords: Language Experience Approach (LEA), motivation, reading, comprehension